2015
DOI: 10.1111/ejh.12284
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F‐FDGPET/CT in the management of Burkitt lymphoma

Abstract: More accurate staging can be achieved using PET/CT. NPV reaches 100%, and using a ΔSUV < 66%, a high PPV is also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…All cases of Burkitt lymphoma are FDG-avid, and PET/CT staging detects more extranodal disease than conventional staging. Of interest, occult bone marrow involvement is found and occasional clinically important upstagings occur [33].…”
Section: Pet/ct Staging In Staging Of Aggressive Non-hodgkin Lymphomasmentioning
confidence: 99%
“…All cases of Burkitt lymphoma are FDG-avid, and PET/CT staging detects more extranodal disease than conventional staging. Of interest, occult bone marrow involvement is found and occasional clinically important upstagings occur [33].…”
Section: Pet/ct Staging In Staging Of Aggressive Non-hodgkin Lymphomasmentioning
confidence: 99%
“…More recently, Carrillo-Cruz et al analyzed the role of 18 FDG-PET at the end of treatment using Deauville criteria. In this heterogeneous study including 13 children and 19 adults and different treatment schemes, the NPV of 18 FDG-PET reached 100% ( 27 ). Our results are consistent with these data and strengthen the literature on a homogeneous population of pediatric BL, in which all residual lesions were biopsied or resected.…”
Section: Discussionmentioning
confidence: 81%
“…In the Bakhshi et al study ( 22 ), response at interim 18 FDG-PET or CI did not predict PFS or overall survival in 34 patients with non-lymphoblastic lymphomas including 28 B-cell lymphomas. In Carrillo-Cruz’s study ( 27 ), the Deauville criteria (score ≥4 as positive) did not allow to predict outcome accurately in a heterogeneous population of BL when quantitated at the end of treatment. On the contrary, in our study, the use of Deauville criteria (score ≥4 as positive) improved specificity and PPV and 18 FDG-PET was predictive of outcome ( p = 0.011) when performed in an earlier setting (after induction chemotherapy).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, novel neuroimaging methods that may improve early diagnosis of the disease, thus improving patient prognosis, are required. In recent years, a number of studies have demonstrated that information provided by 18-fluorodeoxyglucose positron-emission tomography/CT (FDG-PET/CT) may result in greater sensitivity compared with anatomic imaging modalities (18,19).…”
Section: Discussionmentioning
confidence: 99%